IN VITRO CYTOTOXIC AND ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT OF Euglena viridis - B.K. DAS; JYOTIRMAYEE PRADHAN; MAHAMMAD SADIQUE; KAUSALYA KUMARI NAYAK (International Journal of Pharma and Bio Sciences, 2012)
Euglena viridis extract was evaluated for its in vitro cytotoxic activity against two prostate cancer cell line, PC3, Du145 and colon cancer cell line, HCT-116. The ethanolic extract of Euglena was fractionated with hexane and ethyl acetate solvent system. The active partial purified fraction was tested for cytotoxic activity by methyl thiazolyl tetrazolium (MTT) assay. The results showed that 50 μg & 100 μg of algal extract were the most effective concentrations against PC3, Du145, HCT-116 cells. Preliminary phytochemical analysis of the crude extracts was revealed the presence of alkaloid, flavonoid and reducing sugar in ethanolic extracts. Antibacterial activity of the fraction was done by disc diffusion method against nine bacterial pathogens (Pseudomonas putida, P. aeruginosa, P. fluorescens, Aeromonas hydrophila, Vibrio anguillarum, V. alginolyticus, V. fluvialis, V. parahaemolyticus and Escherichia coli). The extract showed highest antibacterial activity against V. anguillarum (20.08±0.561mm) and E.coli (21.33±0.457mm) with lowest minimum inhibitory concentration (MIC) values (40μg/ml & 60μg/ml). From the performed assay the results supports the use of Euglena extract as antimicrobial agents as well as anticancer agents and novel pharmaceutical leads. The alga needs the further investigation for the isolation of its active constituents.